PRODUCT QUALITY TO REPURCHASE INTENTION THROUGH CUSTOMER SATISFACTION AND TRUST, WORD OF MOUTH, AND CORPORATE IMAGE AS MODERATION IN MEDIUM-SCALE CONSTRUCTION BUSINESSES - Novanda Crysma Terrasista; Tony Antonio (LPPM STIE Muhammadiah Bandung, 2025)
The construction sector plays a crucial role in national development, supporting economic, social, and cultural growth. It is expected to grow by 10-15% under the Master Plan for the Acceleration and Expansion of Indonesian Economic Development (MP3EI) until 2025, making it a promising sector for the next decade. PT Catur Eka Manunggal Jaya (PT CEMJ), a construction company based in East Java, was established in 1997 and specializes in real estate and building construction. This study examines the effects of product quality and customer satisfaction on repurchase intention, the impact of product quality on customer satisfaction, the moderating role of trust, word of mouth, and corporate image in the relationship between product quality and customer satisfaction, and the mediating effect of customer satisfaction on the relationship between product quality and repurchase intention. The study involved 70 respondents who are employees of PT CEMJ’s partner companies. Data were collected via Google Forms using a Likert scale and analyzed using SEM-PLS. Results indicate that product quality and customer satisfaction positively and significantly influence repurchase intention, and product quality significantly impacts customer satisfaction. However, trust, word of mouth, and corporate image do not moderate the effect of product quality on customer satisfaction. Furthermore, customer satisfaction mediates the relationship between product quality and repurchase intention, reinforcing the importance of product quality in driving customer loyalty.